ANALYSIS OF UNDERSTANDING CONCEPTS AND OBSTACLES UNDERSTANDING CONCEPTS OF TEMPERATURE AND HEAT MATERIALS IN PHYSICS LESSONS - SIMANJUNTAK, EMMI PUTRI (Universitas Islam Sumatera Utara, 2024)
This research aims to describe the deepening of students' concepts and determine the difficulties experienced by students in the material Temperature and Heat. This survey research was conducted in classes Xll IPA 1 and Xll IPA 2 at Imelda Private High School, Medan. The research carried out used descriptive analysis. Data was obtained through a concept deepening test in the form of multiple choice questions accompanied by reasons. From the survey conducted, it was found that only 37.64% of students were able to answer correctly all the questions given, for the most difficult concept to understand, namely the concept of specific heat with a percentage of 26.5%.